Analisis Budaya Organisasi di Pusat Pendidikan dan Pelatihan Manajemen Pertahanan Badan Pendidikan dan Pelatihan Kementerian Pertahanan - Anindya, Anindya Rianda Putri; Rahman, Abdul (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2025)
This study aims to analyze the organizational culture within the Center for Defense Management Education and Training, under the Education and Training Agency of the Ministry of Defense. Employing a qualitative descriptive approach, the study utilizes Cameron and Quinn’s as its analytical foundation, which categorizes organizational culture into four types: Clan, Adhocracy, Market, and Hierarchy. Data were collected through interviews, observation, and document analysis of the organization’s activities and policies. The findings indicate that the dominant organizational culture type at the Center is Hierarchy, characterized by a clear structure, strict regulations, and an emphasis on stability and control. However, elements of Clan culture are also present, particularly at the operational level, where work relationships tend to be familial and collaborative. These findings suggest that while bureaucratic structures remain prevalent, there are opportunities to enhance efficiency and adaptability by strengthening collaborative and innovative cultural elements. This study is expected to contribute to the development of a more adaptive organizational management model in response to dynamic strategic environments.